Learning Arabic Language Books for Beginners Through the Application of The Imla’ Method - Mappanyompa Mappanyompa; Aidah Mifta; Mufti Rizky; Saba Mansoor (Institut Studi Islam Muhammadiyah Pacitan, 2026)
This study aims to determine the process and effectiveness of learning Arabic texts for beginners through the Imla' method at the Darunnajah Kalikuning Islamic Boarding School (PPTQ). The Imla' method is used as the primary approach because it emphasizes direct listening and writing skills, enabling students to recognize Arabic letter forms, vocabulary, and structure more effectively. This study employed a qualitative, descriptive approach. Data were obtained through observation of the learning process, analysis of student learning activities, and observation of student responses during dictation sessions. The results indicate that learning using the Imla' method occurs in three main stages: preparation, dictation, and evaluation. The teacher introduces new vocabulary, provides pronunciation examples, and dictates words or sentences in a structured manner, repeating them three times. This process is effective in improving students' listening skills, correct Arabic writing, accuracy, and memory. Furthermore, this method fosters discipline and independence through self-evaluation conducted by students after dictation.